BEBERAPA ASPEK SEPUTAR SASTRA WANGI - Khristianto Khristianto (University of Muhammadiyah Purwokerto, 2008)
Sastra wangi or fragrant literature is a call to the literary works composed by female writers. It explores about the life of female characters, and questions about the settled constellation between man and woman in life. The works reflect the woman worldview, especially Indonesian woman, about the realities in the society, particularly on the unfair patriarchal structure positioning the woman in a subordinate level, including in the issue of sexuality. By employing many vulgar words, the works are regarded as a way taken by the writers to protest the unfair world. This article tries to give a glance about the literary phenomenon in Indonesia by relying on the media sources as the first hand catching the actual things. It also sees the genre from some perspectives: feminism, capitalism, and the literary theory.